Cervical radiculopathy management with physical, chiropractic, and acupuncture therapy: Factors associated with different therapy utilization patterns - Anthony E. Seddio, BS; Beatrice M. Katsnelson, BA; Michael J. Gouzoulis, BS; Sahir S. Jabbouri, MD; Anshu Jonnalagadda, BS; Wesley Day, BS; Daniel R. Rubio, MD; Jonathan N. Grauer, MD (North American Spine Society Journal)
Background: Cervical radiculopathy (CR) is a common cervical spine pathology. Following diagnosis, patients may seek conservative management including physical therapy (PT), chiropractic therapy (CT), and acupuncture therapy (AT). Literature supporting alternative management strategies remains limited and mixed, however, their utilization continues to rise. Methods: Patients with a first-time diagnosis of CR were identified from the M165Ortho PearlDiver database. Exclusion criteria included: <18 years of age, concurrent cervical myelopathy, therapy use prior to diagnosis, those with trauma, neoplasm or infection, and <90-days follow-up. Utilization rates and mean PT, CT, and AT sessions within 90-days of CR diagnosis were compared. Clinical and nonclinical predictors of alternative therapy utilization patterns were compared by multivariable logistic regression. Results: Of 789,970 identified CR patients, PT was noted for 132,929 (16.8%), CT for 34,354 (4.4%), and AT for 1,916 (0.2%) within 90-days. CT demonstrated the highest number of sessions (7.81 ± 6.37), followed by PT (7.36 ± 5.54), and AT (5.89 ± 4.97) (p < .05). Predictors of CT utilization, relative to PT were lower age (odds ratio [OR]: 0.84), lower comorbidity burden based on Elixhauser Comorbidity Index (OR: 0.91), region (South OR: 2.05, Northeast OR: 1.93, Midwest OR: 1.92), and insurance (Medicaid OR: 0.30 and Medicare OR: 0.92) (p < .001 for all). Predictors of AT utilization, relative to PT were lower age (OR: 0.93, p < .001), male sex (OR: 1.14, p = .004), region (West OR: 3.31, p < .001, Northeast OR: 2.76, p < .001, Midwest OR: 1.27, p = .002), and insurance (Medicaid OR: 0.29 and Medicare OR: 0.59, p < .001). Conclusions: Within 90-days following newly diagnosed CR, only a minority of patients utilized any form of therapy, despite typically being thought of as a first-line conservative management strategy. Among CR patients who did pursue therapy, PT was more commonly utilized than both CT and AT. The significance of nonclinical drivers of alternative therapeutic strategies suggests a lack of therapeutic consensus at a national level, potential inequities to access, and room for algorithm-driven care pathways.